2022
DOI: 10.3399/bjgpo.2021.0192
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and physicians’ experiences with remote consultations in primary care during the COVID-19 pandemic: a multi-method rapid review of the literature

Abstract: BackgroundDuring the COVID-19 pandemic, many countries implemented remote consultations in primary care to protect patients and staff from infection.AimThe aim of this review was to synthesise the literature exploring patients’ and physicians’ experiences with remote consultations in primary care, during the pandemic, with the further aim of informing their future delivery.Design & settingRapid literature review.MethodWe searched PubMed and PsychInfo for studies that explored patients’ and physicians’ expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 36 publications
5
62
0
Order By: Relevance
“…Technical challenges and worries about difficult conversations in this evaluation reflect the work of others 30 , 31 and Verma and Kerrison's 32 rapid review, which highlights concerns about using the technology required for remote consultation. Both patient and clinician participants in our study were concerned about the technical skills needed for remote consultation and were concerned about internet connections, loading up data or measurements (for example blood sugar or blood pressure) and how secure this was.…”
Section: Discussionmentioning
confidence: 80%
“…Technical challenges and worries about difficult conversations in this evaluation reflect the work of others 30 , 31 and Verma and Kerrison's 32 rapid review, which highlights concerns about using the technology required for remote consultation. Both patient and clinician participants in our study were concerned about the technical skills needed for remote consultation and were concerned about internet connections, loading up data or measurements (for example blood sugar or blood pressure) and how secure this was.…”
Section: Discussionmentioning
confidence: 80%
“…Viewing the patient’s facial expressions during this manual palpation provides a critical source of feedback to assess a range of medical hypotheses for diagnosis. Given the growing shortage of physicians 14 , the chronic issues such as pandemics 15 17 , cost and time cost involved in face-to-face examinations 18 , inaccessibility to examine the patients due to issues such as armed conflicts 19 , the need for remote diagnosis of patients has gained much attention in recent times. Remote palpation examination is one such approach that is growing in interest for remote diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Physical examinations are often performed in-person. However, with the growing shortage of physicians 14 and the considerable challenges of conducting in-person patient examination due to global issues such as pandemics 15 17 , the time cost involved in face-to-face examinations 18 , and inaccessibility to examine the patients due to issues such as armed conflicts 19 , the need for remote diagnosis of patients has gained much attention in recent times. Further, remote diagnosis and treatment reduces the burden on hospitals and the risk of cross-infection during pandemics 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Improving the quality of consultations is more challenging when consulting remotely. Previous research has suggested less rapport building is undertaken during telephone consultations compared to face-to face [ 20 ] and loss of non-verbal communication is a challenge when consulting remotely [ 21 ]. Primary care professions interviewed about their experience consulting during the pandemic, reported feeling that remote consultations created emotional distance between themselves and patients [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Improving the quality of consultations is more challenging when con remotely. Previous research has suggested less rapport building is undertaken telephone consultations compared to face-to face [20] and loss of non communication is a challenge when consulting remotely [21]. Primary care prof interviewed about their experience consulting during the pandemic, reported feeli remote consultations created emotional distance between themselves and patien Video consultations may be superior to telephone in enabling rapport to be built [2 Eight percent of patients who were not offered the option of a support person have liked this to have occurred, highlighting a missed opportunity.…”
Section: Comparison To Other Studiesmentioning
confidence: 99%